Effectivity of Normal Concrete and Clamshell as Materials of Artificial Pyramid Reef at Pasir Putih Beach, Situbondo - Indonesia - Rudhy Akhwady; Muhammad Akhyar Maududi; Dwi Chandra Dewi; Oktiyas Muzaky Luthfi (Politeknik Kelautan dan Perikanan Dumai, 2021)
The bivalve anadara grandis is one of the most abundant shells which are easy to find in Indonesian waters. The number of clams consumed is directly proportional to the amount of clamshell waste, which the most part is only disposed into waste. Coral reef has a very important purpose in supporting activities in coastal areas. Artificial reef is a structure that has aim to restore the biological purpose coral reef that have been damaged. This study aims to compare the effectiveness of the use of normal concrete (made from sand, cement dan splits only) than clamshell mixture as materials of artificial reef. A field research was conducted in Pasir Putih, Situbondo, with visual descriptive method (transect with a quadrant of 25 x 25cm) and underwater camera as an aid to facilitate the observation. During the 4-month observation of the drowning, nine types of biotas were found in attaching, with the dominant biota attached to these artificial reef were bivalves, barnacles, and bryozoan. Results show that the total number and density of calcareous biota attached on clamshell concretes are higher than those of standard concretes. So, it could be concluded that the concrete reefs made of clamshells resulted in attachment of biota slightly higher than it of normal concretes and the benefits of both materials can form the coral reef ecosystem well. In particular, the use of artificial reef with a mixture of clamshells is better than normal concrete because its more effective for algae attachment and cheaper because low budget due to the material availability of clamshell presently as damage and wastes in coastal area.